PENGEMBANGAN MEDIAPEMBELAJARAN INTERAKTIF MENGGUNAKAN MACROMEDIA FLASH 8.0 BERBASIS ANDROID PADA POKOK BAHASAN TRANSFORMASI KELAS XI SMA - Adik Reza Mufidah; Dwi Rahmawati; Yeni Rahmawati ES (EMTEKA: Jurnal Pendidikan Matematika, 2022)
This study has the objectives: to determine the process of developing interactive learning media using Android-based macromedia flash 8.0 on the subject of transformation of class XI SMA, and to find out the validity and practicality of interactive learning media using Android-based macromedia flash 8.0 on the subject of transformation of class XI SMA. The research uses the ADDIE development model, but this development is limited to four stages, namely Analyze, Design, Development, and Evaluation. The instruments used were interview guidelines, validation questionnaires, and student response questionnaires. The research results obtained are. Interactive learning media using Android-based macromedia flash 8.0 on the subject of transformation of class XI SMA is declared very valid with an average of 85.18% and very practical with an average of 95.23%. This development has the conclusion that interactive learning media using macromedia flash 8.0 based on android on the subject of transformation of class XI SMA is very valid and very practical to use.